An evaluation of the relationship between ethical leadership and employee performance - Paul Motampe Mpye (IJEBD (International Journal of Entrepreneurship and Business Development))
Purpose: The unethical conduct of higher education tertiary institution leaders influences organisational and individual employee performance. Employees in Technical and Vocational Education and Training (TVET) colleges have been victims of ineffective leadership styles. Therefore, the current study aimed to investigate the relationship between ethical leadership and employee performance in public sector TVET colleges in Gauteng Province, South Africa.